Meningkatkan Pemahaman Siswa Terhadap Operasi Penjumlahan Bilangan Pecahan Dengan Menggunakan Gambar Luas Daerah Di Kelas IV SD Inpres Maccini Sombal Kota Makassar - Latri Aras; Rahmawati Patta; Bahar Bahar (Prodi PGSD FIP UNM, 2017)
This research is a class action that includes planning, implementation, obervation, and reflection. Data in the research are data activity and students learning outcomes in the addition fractions. Data obtained by obervation, testing, field notes which aims to improve understanding of the add fractions by using an image area of fourth grade students SD Inpres Maccini Sombala Makassar. The benefits of this research are (1) to provide direct experience of the ability of comprehensive applications of the use of the image area in an effort to improve the capability of addition fractions, (2) as an improvement of teaching on the subject of the addition fractions. The results of this research are the first cycle that (1) presenttasion on stage percentage in wide image the area is not maximized, (2) students has diffuculty in summing fractions, and (3) working group has not been maximized. While in the second cycle has that significant improvement; (1) presentation on stage percentage in wide image the area has a maximum running in accordance with the plan, (2) the students has mastered fractions addition operation using the image of area, and (3) students can work in groups optimally operate the sum fractions by using a wide image area. The improvement can be seen in the fisrt cycle qualifications less (K), the second cycle qualification of good (B). The conclusions of this research is to use the image in the area of learning fractions can enhance students undertanding fourth grade SD Inpress Maccini Sombala Makassar.Keyword: fractions, additions, wide of image the area